El ventall de la societat del seu temps segons Ramon Llull - Ensenyat Pujol, Gabriel (Acta Hispanica, 2016)
The tripartite scheme based on the three orders (oratores, bellatores and laboratores), which characterized the society in the early Middle Ages, was already obsolete in the 13th century, since by this time the social structure had become much more complex. Furthermore, the presence of new social groups, such as the merchants and the bourgeois, raised a debate about its “raison d’être”. Therefore a person such as Ramon Llull, who knew very well the world where he lived, described a more representative image of the society of his time. Moreover, the interest of his analysis goes even further, since the Blessed took sides for some groups, such us the merchants –whose activity had been condemned until that moment– or the farmers, usually reviled. He even incorporates in his analysis some groups of people, such as the pilgrims or the painters, missing in any other work of the time.